Pelatihan Pendampingan Pembuatan Peta Tematik Menggunakan GPS dan Aplikasi CAD - Andrew Stefano; Sri Endayani (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2020)
One of the problems in the development of human resource professionalism so far is related to land issues (boundaries). The purpose of this activity is to provide training on the use of GPS and processing data using Autodesk map software. The training was attended by the village and sub-district staff of Samarinda City, as many as 50 people. The method used is 1) giving theoretical and practical knowledge about data collection and processing 2) assignment of making land boundaries per area, 3) presentation of results in the field and 4) output (boundary map). The results of this activity were: First, all participants of this training activity were very enthusiastic, enthusiastic, and had high motivation to take part in the implementation of the second boundary land making training activity, the participants who succeeded in making a land boundary map of 25 people or 50% of 50 participants. Third, the quality of the maps is quite good. They found differences in boundary map shape between version Samarinda City Bappeda and field data collection. Based on field data from the Bugis Kelurahan staff, the shape of the land boundary map in the Bugis sub-district in Samarinda almost resembles the land boundary map of Samarinda City of 2.5 ha, because Samarinda City Bappeda does not include the Segiri GOR Stadium as an area of Bugis sub-district that should be included as a map of the border. The map results from Samarinda Kota sub-district staff were recombined by sub-district and sub-district lurah to be determined as a map of sub-district Kota Samarinda and displayed in the A0 printout in each of the kelurahan offices located in sub-district Samarinda Kota.